Socio-Economic Factors and Tourism – Impact Analysis using Indicator Approach - Anuja Lokeshwara; Nagalingam Nagendrakumar; Karanasuriya Ragalage Ganguli Thamodya Jayasuriya; Hewissa Gamage Anuradha Malith Ravisara; Matheesha Jeewantha Weerawickrama; Madawala Gamage Dhanushka Madushan (Centre For Tourism Planning and Development, 2023)
The study uses an indicator approach to assess the socioeconomic impact on tourism in developing countries, using Sri Lanka as a case. Tourism is a flourishing sector in Sri Lanka that was affected by different aspects such as pandemics, terrorism, and economic, social, and political instabilities. Though the effects of these events have been studied separately, studies done to assess the socio-economic impact of tourism in Sri Lanka using an indicator approach are scarce; hence the study aims to fill this prevailing knowledge gap. Based on data availability, the study uses secondary data from Sri Lanka Tourism Development Authority and Central Bank reports of Sri Lanka from 2010 to 2019. The socio-economic impact of tourism is measured using integral indicators calculated using the coefficients and weights of the data collected. The study concludes that tourism in Sri Lanka has had a positive socioeconomic impact and has increased continuously since 2010 except in 2019, due to the aftermath of the Easter Sunday attacks in April 2019. This study indeed provides a stepping stone to study the Sri Lankan Tourism Sector which is currently going through political and economic turmoil.